The Students’ Perception of Using OME TV Application as Media to Practicing English Speaking - Putra, Rangga Mega (International Journal on Advanced Science, Education, and Religion, 2025)
The objective of this study was two fold: to examine the speaking abilities of seventh-grade students at SMP Ma'arif NU 4 Darurrohmah using Ome TV-based media, and to assess the improvement in these abilities resulting from this intervention. This research employed Classroom Action Research (CAR) methodology, conducted in two cycles, each encompassing planning, action, observation, and reflection. Both quantitative and qualitative data were collected, with tests serving as the primary assessment instrument. The study population consisted of all seventh-grade students at SMP Ma'arif NU 4 Darurrohmah, from which a purposive sample of 30 students from class 7.1 was selected. The findings indicated a significant enhancement in the students' speaking abilities in relation to conversation materials following the implementation of Ome TV-based media. Notably, students not only improved their vocabulary but also reported a more enjoyable learning experience. In the pre-test, 10 students (33%) achieved scores above 75. This number increased to 15 students (50%) in the post-test of Cycle 1, and further to 25 students (83%) in the post-test of Cycle 2. These results highlight a substantial improvement in the students' speaking capabilities. It indicated date, the integration of Ome TV-based media proved effective in enhancing the speaking abilities of students, particularly in the context of conversation materials, thereby affirming the success of the research. Keywords: English Speaking, Students’ Persception, Ome tv